Effects of different modified atmosphere treatments on lipid oxidation in spiced beef at different storage temperatures. Issue 3 (23rd January 2021) - Hai, Dan; Huang, Xianqing; Song, Lianjun
Abstract: The high moisture and nutrient contents of spiced beef make it popular with consumers but present challenges for its storage, as spoilage is a common phenomenon. Therefore, for identifying packaging methods to reduce spoilage during storage, this study investigated the effects of 5% O2 (low oxygen), 70% CO2 (high carbon dioxide), and 5% O2 /70% CO2 /25% N2 (compound group) on lipid oxidation in spiced beef in the test groups and a vacuum‐packed group (control) at storage temperatures of 4, 25, and 60°C. The pH, thiobarbituric acid (TBA), anisidine value (AV), and peroxide value (POV) of the spiced beef were determined. Results indicated that 70% CO2 and storage at 4 and 25°C showed the strongest ability to inhibit the rancidity in spiced beef. The 5% O2 group delayed both initial oxidation and secondary oxidation of lipids. Although the compound group significantly inhibited the rancidity in spiced beef at 60°C, it could not maintain such inhibition for long. Among all the groups, the 70% CO2 group demonstrated maximum inhibition of initial lipid oxidation and suppressed the secondary oxidation of lipids for the longest time. Thus, the modified atmosphere packaging with O2 and CO2 can regulate the fat oxidation in meat products and effectively improve their flavor maintenance. Abstract : Spiced beef is a traditional Chinese cooked food product, and research on the mechanism of lipid oxidation of spiced beef in foreign countries is lacking. Atmosphere packaging technology was used for the first time for the preservation of traditional Chinese spiced beef. The effect of single gas component (5% O2/95% N2, 70% CO2/30% N2) on lipid oxidation of spiced beef was studied.